Application and Prospect of Postmortem Imaging Technology in Forensic Cardiac Pathology: A Systemic Review - Ningguo Liu; Mingzhen Yang; Zhling Tian; Hewen Dong; Yang Lu; Donghua Zou; Yanbin Wang (Wolters Kluwer Medknow Publications, 2022)
Postmortem imaging (PMI) technology known as virtual autopsy or virtopsy is regarded as a useful method of noninvasive or minimally invasive autopsy in forensic practice. Postmortem computed tomography is applicable to traumatic investigation, acute hemorrhage, pulmonary parenchyma disease, calcification (calculus, atherosclerosis), and gas accumulation. Postmortem magnetic resonance (PMMR) has been proven to have advantages in soft tissue identification. Cardiac death is one of the keys and difficult points in forensic practice. With the introduction and development of PMCT angiography and PMMR, it was proved to be a very promising tool in the investigation of cardiac death, including vascular cavities and ischemic myocardium. This article reviewed the applications of the latest PMI and its related technologies in forensic cardiac pathology, including advantages, limitations, and development prospects.